The Application of Brain-Computer Interface in Upper Limb Dysfunction After Stroke: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Peng, Yang; Wang, Jing; Liu, Zicai; Zhong, Lida; Wen, Xin; Wang, Pu; Gong, Xiaoqian; Liu, Huiyu (Frontiers in Human Neuroscience, 2022)
Objective: This study aimed to examine the effectiveness and safety of brain-computer Interface in the treatment of upper limb dysfunction after stroke. Methods: English and Chinese electronic databases were searched up to July 2021. Randomized controlled trials (RCTs) were eligible. The methodological quality was assessed using Cochrane’s risk of bias tool. Meta-analysis was performed using RevMan 5.4. Results: A total of 488 patients from 16 rcts were included. The results of the meta-analysis showed that ①The meta-analysis of BCI combined treatment on improvement of upper limb function showed statistical significance (SMD: 0.53, 95% CI: 0.26 to 0.80, P < 0.05). ②BCI treatment can improve the abilities of daily living of patients after stroke, and the analysis results are statistically significant (SMD: 1.67, 95% CI: 0.61 to 2.74, P < 0.05). ③BCI combined therapy was not statistically significant for the analysis of MAS (SMD: -0.10, 95% CI: -0.50 to 0.30, P = 0.61). Conclusion: The meta-analysis indicates the BCI therapy or BCI combined with other therapies like conventional rehabilitation training and motor imagery training can improve upper limb dysfunction after stroke and enhance the quality of daily life.